Risk assessment and risk modelling in geothermal drilling - Lilian Aketch Okwiri 1986- (2017)
Development of geothermal energy has advanced in the last few years and will continue to do so in the coming years. But this development is slowed by the high risks and costs associated with the drilling phase of geothermal development. The goal of this study was to find out the risk factors that can interrupt or delay the delivery, or compromise the quality of a geothermal well and how these risks are perceived by drilling professionals in Iceland and in Kenya. Sixty-four (64) risk factors were identified, an online questionnaire developed and the survey tool QuestionPro used to send out the survey. The results showed that drilling risk analysis is subjective and risks are ranked, or perceived to be high or low, depending on the project setting such as physical, economic and political environments. Generally, toxic gas release was ranked the highest risk for drilling operations, followed by high cost of drilling and lost circulation. The second part of the study looked at the value of integrated cost and schedule risk in execution of drilling projects, allowing for accurate budget and schedule estimation. The project risk management software RiskyProject was used for this purpose to simulate a sample drilling project. The results show that cost and schedule risk management can play an important role in geothermal drilling projects. The deterministic method of costs and schedule estimation commonly in use could easily result in cost and schedule overruns or underruns due to the influence of risks and uncertainties encountered within and outside the project. A Monte Carlo simulation run on the sample drilling project showed that the P50 values giving the most likely values for cost and schedule, gave a higher value than the base values determined for the project. P1/P99 range was 1,115,369 USD for cost and 343 hrs for schedule. The simulation showed that drilling the 8½" section has the largest influence on the well completion time and therefore greater effect on the cost and schedule of the drilling project. For ...